A broad-spectrum inhibitor of copper-exporting P 1B -type ATPases - Vinit C. Shanbhag; Samuel Anakpeba-Dinguyella; Nikita Gudekar; Kristyn Conrad; Chiemerie Azubuogu; Corinna Probst; Martina Ralle; María G. Mediavilla; Julia A. Cricco; Natalie M. Garza; Vishal M. Gohil; Scott Peck; et al. (Proceedings of the National Academy of Sciences, 2026)
Copper (Cu) transporting ATPases represent a highly conserved subclass of P-type ATPases with critical roles in Cu export and metalloenzyme synthesis. Despite their important biological roles and association with a wide range of human diseases, no high-affinity small-molecule inhibitors have been described. Here, we identify MKV3 as a small molecule inhibitor of Cu-transporting P-type ATPases that targets a conserved Cu + entry site to the translocation pathway. In silico docking against the Xenopus ATP7B structure revealed a highly conserved pocket suitable for pharmacological inhibition. MKV3 bound human ATP7A and ATP7B with nanomolar affinity, competed with N-terminal metal-binding domains for access to the Cu + entry site, and selectively inhibited Escherichia coli CopA ATPase activity and Cu + transport. Mechanistically, MKV3 blocked chaperone-mediated Cu + delivery to the intramembranous CPC site of CopA that is essential for its transport function. We further identified a single charged P-domain residue that governed MKV3 affinity and potency across species. Functionally, MKV3 phenocopied the genetic loss of Cu + -ATPases in bacteria, fungi, plants, zebrafish, and mammals, impairing copper-dependent enzymes, transporter trafficking, and copper tolerance. These findings establish a conserved, druggable vulnerability in Cu + -ATPases and introduce MKV3 as a broadly active chemical tool to modulate copper homeostasis across biological kingdoms.